Liposomes –A Overview - Patel, Akshay Kumar; Mutta, Shivanand K; Yadav, Rajkumar Prasad (Asian Journal of Pharmaceutical Research and Development, 2021)
Liposomes are sphere-shaped vesicles made up of one or more bilayers of phospholipids. The ability of delayed vesicles to transport medications, vaccines, diagnostic specialists, and other bioactive operators has accelerated development in the liposomal drug delivery system. The liposomal delivery system's pharmacyelements and pharmacokinetics properties have been altered, resulting in a higher therapeutic index and lower overall toxicity. There are many factors to consider, including size, size distribution, surface electrical potential, lamella count, and encapsulation efficacy. The use of surface modification in the development of liposomes with various mechanisms, kinetic properties, and biodistribution was discovered to be beneficial. Drug delivery, drug targeting, controlled release, and improved solubility have all been studied extensively with liposomes.